Mechanistic Insights into Reprogramming to Induced Pluripotency - Ho, Ritchie (2011)
Induced pluripotent stem (iPS) cells can be generated from various embryonic or adult cell types upon expression of a set of few transcription factors, most commonly consisting of Oct4, Sox2, c-Myc and Klf4, following a strategy originally published by Takahashi and Yamanaka in 2006 (Takahashi and Yamanaka, 2006). Since iPS cells are molecularly and functionally similar to embryonic stem (ES) cells, they provide a source of patient-specific pluripotent cells for regenerative medicine and disease modeling, and therefore have generated enormous scientific and public interest. The generation of iPS cells also presents a powerful tool for dissecting mechanisms that stabilize the differentiated state and are required for the establishment of pluripotency. In this review, we discuss our current view of the molecular mechanisms underlying transcription factor-mediated reprogramming to induced pluripotency.